Undisciplined Reviewed From the Habitus Pierre Bourdieu Theory - Mustofa, Mustofa (The Journal of Society and Media, 2019)
The background undisiciplined attitude of students is found in daily life such as being late to class, littering, breaking traffic and other undisciplined attitudes. Though discipline is an important factor that determines success in the future. This study aims to uncover and explore the underlying causes of undisciplined attitudes in student life. Then explain and provide solutions to get used to the discipline in life. This study focuses on undisciplined attitudes that occur among students of the Nahdlatul Ulama University of Surabaya by determining the sample. This research uses descriptive survey method. The sample was taken from the representation of students in each faculty totaling 6 Faculties so that the data obtained varied. The average sample is 25 students from each faculty. The results showed that all students who were given the questionnaire were undisciplined in their daily lives. In conclusion Undisciplined attitude due to environmental influences (objectivism) and low self-awareness (subjectivism), which is in harmony with Pierre Bourdieu's habitus theory.